Hijacking Cellular Stress Responses to Promote Lifespan - Dutta, Naibedya; Garcia, Gilberto; Higuchi-Sanabria, Ryo (Frontiers in Aging, 2022)
Organisms are constantly exposed to stress both from the external environment and internally within the cell. To maintain cellular homeostasis under different environmental and physiological conditions, cell have adapted various stress response signaling pathways, such as the heat shock response (HSR), unfolded protein responses of the mitochondria (UPRMT), and the unfolded protein response of the endoplasmic reticulum (UPRER). As cells grow older, all cellular stress responses have been shown to deteriorate, which is a major cause for the physiological consequences of aging and the development of numerous age-associated diseases. In contrast, elevated stress responses are often associated with lifespan extension and amelioration of degenerative diseases in different model organisms, including C. elegans. Activating cellular stress response pathways could be considered as an effective intervention to alleviate the burden of aging by restoring function of essential damage-clearing machinery, including the ubiquitin-proteosome system, chaperones, and autophagy. Here, we provide an overview of newly emerging concepts of these stress response pathways in healthy aging and longevity with a focus on the model organism, C. elegans.